2008
DOI: 10.1128/aac.00424-08
|View full text |Cite
|
Sign up to set email alerts
|

Disposition, Metabolism, and Excretion of [ 14 C]Doripenem after a Single 500-Milligram Intravenous Infusion in Healthy Men

Abstract: In this open-label, single-center study, eight healthy men each received a single 500-mg dose of Doripenem is a new parenteral carbapenem antibiotic with broad-spectrum activity against gram-negative and gram-positive pathogens, including strains resistant to multiple antibiotic classes (1, 6, 7). It is indicated for adults in the treatment of complicated intra-abdominal infections and complicated urinary tract infections, including pyelonephritis. Doripenem exhibits in vitro activity against contemporary stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
36
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 16 publications
5
36
2
Order By: Relevance
“…However, this estimate is notably lower than that previously described in healthy volunteers (0.22 to 0.25 liters/kg/h) (34,35) and noncritically ill patients (0.16 to 0.25 liters/kg/h) (8,(36)(37)(38). The differences were expected, as the noncritically ill population would presumably have better end-organ function than our patient cohort.…”
Section: Discussioncontrasting
confidence: 53%
See 2 more Smart Citations
“…However, this estimate is notably lower than that previously described in healthy volunteers (0.22 to 0.25 liters/kg/h) (34,35) and noncritically ill patients (0.16 to 0.25 liters/kg/h) (8,(36)(37)(38). The differences were expected, as the noncritically ill population would presumably have better end-organ function than our patient cohort.…”
Section: Discussioncontrasting
confidence: 53%
“…Typical V (V 1 ϩ V 2 ) of doripenem in our cohort was 0.47 liters/kg (range, 0.14 to 1.7 liters/kg), which is generally consistent with other reports in critically ill patients with conserved renal function (0.30 to 0.54 liters/kg) (7,9,18,33). This estimate is considerably larger than that previously described in healthy volunteers (0.22 to 0.24 liters/kg) (34,35) and noncritically ill patients (0.18 to 0.24 liters/kg) (17,(36)(37)(38). This was anticipated, as the V of hydrophilic antibiotics, such as aminoglycosides (39,40) and beta-lactams (12), is often reported to be 2-fold greater in critically ill patients.…”
Section: Discussionsupporting
confidence: 40%
See 1 more Smart Citation
“…detected only one metabolite in the urine, the ring-open lactam. Iolanda Cirillo et al [23] reported the metabolism of doripenem in urine. In this work, the electrochemical behaviour of the metabolites of DPM and MPM has been studied, the reduction mechanism has been suggested on the modified electrode and differential pulse voltammetry method have been offered and applied to the determination of DPM and MPM in human urine and serum samples [24].…”
Section: Introductionmentioning
confidence: 99%
“…10) Therefore, the importance of individualized approaches to dosing of drugs, especially renally excreted drugs, in critical ill patients has been highlighted. Doripenem is excreted renally, 11) and is frequently used for critically ill patients in ICU. However, there is a lack of studies validating the dosage regimen based on PK/PD index of DRPM for these patients.…”
mentioning
confidence: 99%